Cobalt nickel boride as an active electrocatalyst for water splitting. Issue 24 (31st May 2017) - Xu, Ning; Cao, Guoxuan; Chen, Zhengjun; Kang, Qing; Dai, Hongbin; Wang, Ping
Abstract : The Co–Ni–B@Ni foam catalyst prepared by a simple electroless plating method exhibits high and stable electrocatalytic activity towards the water splitting. Abstract : Electrochemically splitting water to produce clean hydrogen fuel requires high-performance electrocatalysts. Here, we report that ternary transition metal boride Co–Ni–B is an active candidate catalyst for water splitting. The Co–Ni–B nanoparticles were deposited on Ni foam (NF) by a facile electroless plating method. After being properly calcined under an Ar atmosphere, the Co–Ni–B@NF catalyst exhibits a low overpotential along with high stability in alkaline solutions for the oxygen evolution reaction, which is among the best reported levels for non-precious metal catalysts. Furthermore, the properly annealed Co–Ni–B@NF catalyst also shows good activity towards the hydrogen evolution reaction. The potential of Co–Ni–B@NF as a bifunctional catalyst for the overall water splitting was demonstrated, with 10 mA cm −2 achieved at 1.72 V. The favorable combination of high catalytic activity, facile preparation and low cost makes Co–Ni–B@NF a very promising bifunctional catalyst for electrochemical water splitting.